7 Ritos de passagem de uma bruxa urbana: performances para germinar floresta em um corpo pavimentado - Coelho, Natália Lopes (2023)
In this thesis, a blend of narrative and reverie, I weave tales about a witch-body that works performative spells, creating magic to alter my urban circumstance and, consequently, perhaps the surroundings as well. There are 7 rites of passage of an urban witch, as named within the context of this research, marking my journey as a body artist from 2014 to 2022 through this same number of performances activated in São Paulo and Fortaleza. This path is divided into two non-symmetrical portions mediated by the work Wild Hunt (2018), where I perform in total darkness of the theater, and from which my body will disappear in subsequent works, giving way to the activation of other art/materialities. All these enchantments are created with the intent of shattering the symbolically concreted space that our culture reserves for the feminine, the forest, and beings that diverge from the normativity. Using as the primary material for artistic creation the daily gestures of a woman in the city, this research in art aims to transform concretized habits into forest rites. Through performance, it seeks to act as weeds do when they sprout in the cracks of the sidewalks (BEY, 2013b). The performative rituals of the urban witch are intended to crack the paved states of consciousness, creating patches of visible earth in the midst of the extensive concrete landscape of the city, also understood as an environment. Thus, perhaps, the forest may thrive in the urban environment, and with it, the diversity of be- ings and modes of existence may resurge, as Ailton Krenak warns, before the Earth con- tinues on its course, leaving us behind.